PENGARUH DAYA TARIK IKLAN, KUALITAS PESAN IKLAN, FREKUENSI PENAYANGAN IKLAN, TERHADAP EFEKTIFITAS IKLAN TELEVISI SPRITE - Dicky Anhar (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The results showed that the attractiveness of advertising, the quality of the message, and how often your ad positive and significant impact on the effectiveness of advertising, either partially or simultaneously. With the acquisition of the largest coefficient of 0.399 on the frequency of ad serving on the effectiveness of advertising. Then a number of times better advertising will further improve the effectiveness of ads. Thus PT. Coca-Cola Bottling Indonesia must consider three factors are variable, especially in the variable quality of the message to produce an effective advertisement in accordance with the huge costs that have been incurred. Keywords: advertising appeal, the quality of the message, the frequency of ads, and ad effectiveness